The Impact of Financial Development on Investment: a Review of International Literature - Muyambiri, Brian; Odhiambo, Nicholas M. (Organizations and Markets in Emerging Economies, 2018)
This article summarises the empirical literature on the impact of financial development on investment. It presents a topical analysis of empirical research that focuses mainly on the interaction between financial development and investment, determinants and measurement of both financial development and investment, and empirical findings on the relationship between the two variables under discussion. The study concludes that most of the research done on the relationship between financial development and investment is highly skewed towards assessing the relationship using mostly bank-based financial development indicators, as compared to the market-based financial development indicators. Given the number of studies assessed, the impact of financial development on investment appears to be inconclusive, at best. Moreover, the study shows that the relationship between these two macroeconomic variables seems to differ from country to country; it is dependent on the proxies used to measure the level of financial development, as well as the methodology employed.
Keywords: finance-investment nexus; financial development; investment